Bidirectional DC-DC converter with extended voltage conversion ratio for energy storage applications - Hasani A.H.; Mansor M.; Kumaran V.; Mahmood Zuhdi A.W.; Jia Ying Y.; Hannan M.A.; Azlee Hamid F.; Abd Rahman M.S.; Ashida Salim N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Energy storage; MATLAB; Microgrids; Switched capacitor networks; Bidirectional DC-DC converters; Coupled inductor; Energy storage applications; MATLAB/ SIMULINK; Number of components; Steady-state analysis; Voltage boosting; Voltage conversion ratio; DC-DC converters